2022
DOI: 10.3390/foods11203263
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Bioactive Compound Extraction from Eggplant Peel by Response Surface Methodology: Ultrasound-Assisted Solvent Qualitative and Quantitative Effect

Abstract: Anthocyanin pigments, which the peel of eggplant is rich in, contribute to food quality because of their function in color, appearance, and nutritional advantages. For the first time, this study aimed to optimize the composition of the extracting solvent as three factors: factor A (ratio of ethanol to methanol 0–100% v/v), factor B (ratio of water to alcohol 0–100% v/v), and factor C (citric acid in the final solvent 0–1% w/v) using response surface methodology (RSM), central composite design (CCD) with α 2, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Although there is little research about the use of ultrasound technology for extracting phenolic compounds [ 27 , 28 ], it has been applied previously to apple pomace with other aims such as isolating xyloglucans [ 29 ], or extracting pectin [ 30 ]. Further, ultrasound technology for optimizing the extraction of bioactive compounds has been performed by other authors in other matrices such as eggplant [ 31 ], orange peel [ 32 ], tangerine [ 33 ], cashew apple bagasse [ 34 ] or onion leaves [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although there is little research about the use of ultrasound technology for extracting phenolic compounds [ 27 , 28 ], it has been applied previously to apple pomace with other aims such as isolating xyloglucans [ 29 ], or extracting pectin [ 30 ]. Further, ultrasound technology for optimizing the extraction of bioactive compounds has been performed by other authors in other matrices such as eggplant [ 31 ], orange peel [ 32 ], tangerine [ 33 ], cashew apple bagasse [ 34 ] or onion leaves [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The sonication was accomplished with an ultrasonic transducer and a power supply (HAMEG 8150, Mainhausen, Germany). Sonication enhances bioactive compound extraction by facilitating mass transfer from pomace to solvent and improving fluid dynamics along the extraction column [13]. Subsequently, the liquid part of the extract was evaporated under vacuum at 40 • C using an evaporator.…”
Section: Raw Materials and Sample Extract Preparationmentioning
confidence: 99%
“…At 517 nm, the absorbance was determined spectrophotometrically. The scavenging ability of the plant extract was calculated as the following [13][14][15][16].…”
Section: Dpph Radical Scavenging Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with traditional techniques, it has the advantages of being highly efficient, instantaneous, safe, environment-friendly, and having low economic cost. Studies have shown that ultrasound treatment (UT) accelerates the diffusion process, shortens the curing time, positively affects mass transfer during the curing process [ 17 , 18 ], reduces the salt content, and improves the quality of low-salt cured meat products [ 19 ]. Moreover, UT can improve protein properties by reducing particle size and promoting the de-folding of secondary structures, thus improving product characteristics [ 20 ].…”
Section: Introductionmentioning
confidence: 99%